Olfactory enrichment using a maternal pheromone improved post-weaning pig performance and behavior - Archer, Courtney; Garcia, Arlene; Henderson, Madelyn; McGlone, John J. (Frontiers in Veterinary Science, 2022)
The post-weaning environment in commercial pig nursery buildings is typically devoid of both the sow and her semiochemicals. Among other factors, the loss of maternal odors may contribute to post-weaning stress. In this work, we report four studies (studies 1-4) using 192 weaned pigs to evaluate the effects of a maternal pheromone (MP) containing Myristic Acid and Skatole on weaned pig behavior and performance. Study 1 examined behavior among weaned pigs with a focus on lying, aggression and feeding behaviors. All studies used body weight gain and the percentage of pigs that lost weight the first 7 days after weaning as key response variables. The MP stimulated early feeding behavior and reduced aggressive behaviors among weaned pigs (p < 0.01). In study one, pigs were over 4 kg heavier 16 weeks post-weaning when the MP was present for 48 hours post-weaning compared to control pigs (p = 0.05). The three other studies used a 7-day bioassay to assess the best dose and form of delivery of the MP among weaned pigs. The single measure that responded uniformly was the percentage of pigs that lost body weight in the first 7 days after weaning. Among control pigs in four separate studies, 25% of the weaned pigs in each study lost body weight by 7 days after weaning, while in 3 of the 4 bioassay studies, 0% of MP-exposed pigs lost weight after weaning (one study had 6% of pigs losing body weight with the MP). This MP effect is both highly statistically significant and, if found on commercial farms, would have a large positive economic benefit. Simultaneously, having fewer pigs losing weight and exhibiting less aggressive behavior will improve the health and welfare of weaned pigs. Providing biologically-relevant olfactory enrichment can improve pig health and welfare.